Dendritic cell-based immunotherapy for head and neck squamous cell carcinoma: advances and challenges - Chen, Wenyue; Li, Zhengqiang; Tang, Jin; Liu, Shuguang (Frontiers in Immunology, 2025)
Head and neck squamous cell carcinoma (HNSCC) is a prevalent cancer with poor response to conventional treatments such as surgery, chemotherapy and radiotherapy. Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of HNSCC, but many patients still exhibit poor responses due to insufficient T cell infiltration and impaired dendritic cell (DC) function within the tumor microenvironment. DCs are crucial for initiating anti-tumor immune responses, but their dysfunction in HNSCC leads to inadequate T cell activation and immune evasion. DC-based immunotherapy offers a promising approach to enhance ICIs therapy efficacy by improving DC function and enhancing T cell-mediated anti-tumor immune response. This review discusses the mechanisms underlying DC dysfunction in HNSCC, recent advances in DC-based immunotherapy, and the potential for combination therapies to overcome resistance to ICIs. Future strategies should focus on optimizing DC vaccines and developing personalized treatments to improve outcomes for HNSCC patients.